Composición esterólica de la esponja marina xestospongia muta (1985)
ABSTRACT: Two sterol fractions XMl (Rf =0.28, Si02/Benzene: EtO AC 10:2) and XM2 (Rf = 0.24, S;02/Benzene : EtOAc 10:2) were isolated from the marine sponge Xestospongia muta collected at -25 m off Santa Marta bay, Colombian Caribbean Coast. Both sterol mixtures were fractionated by preparativo HPLC and then analyzed by GC and GC-MS. Fourteen sterols were separated and 13 were identified. 3B -OH-A^ -Sterols afforded the most abundant sterols (About 87% of the total sterols) including the novel epimeric mixture (24R -i- 24S)-5,28-Stigmastadien- 3i3-24-diol. Rest of sterols corresponded to Stanols and to a 6.2% of unidentified compounds.